A thousand words about the link between red blood cell distribution width and heart failure - Nowinka, Pawel; Korab-Karpinski, Eduoard; Guzik, Przemysław (Journal of Medical Science, 2019)
A link between the red blood cell distribution width (RDW) and clinical outcomes in heart failure (HF) was reported for the first time in 2007. Since then, many studies have shown that an increased RDW is an independent and strong predictor of mortality and morbidity in patients with acute, decompensated or chronic HF. The evidence for such a link comes from dozens of prospective and retrospective studies in which clinical data from hundreds or even thousands of patients were examined. Although many processes such as nutritional deficiencies (e.g. iron, folate, vitamin B12), inflammation (interleukin 6, tumour necrosis factor), malnutrition, renal failure or tissue and organ hypoxia have been proposed, no clear explanation exists or is commonly accepted. This mini‑review summarises the clinical evidence on the increased RDW as a predictor of adverse clinical outcomes in HF patients, and hypothetical mechanisms that might be responsible for this interesting clinical observation.